Corporate Social Responsibility Disclosure in Moderate the Relationships of Financial Distress and Leverage to Investment Decision - Juliansyah, Athira; Zulfikar, Z (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study seeks to investigate the effect of financial distress and leverage on investment decisions, with CSR Disclosure (CSRD) Disclosure serving as a moderating factor. Methodology: This study focuses on manufacturing companies, which are selected because of the diversity and complexity of their sectors. The manufacturing sector encompasses the basic and chemical industries, various industries sectors, and consumer goods industries sectors. The population taken was 220 companies and the sample size consisted of 60 companies with a total of 167 data taken with 7 outlier data, so the total data taken was 159. The secondary data used in this study was gathered from the sustainability and financial reports of manufacturing companies that were listed between 2018 and 2022 on the Indonesian stock exchange (IDX). Multiple linear regression analysis, hypothesis testing, descriptive statistics, and traditional assumption tests are among the analysis methods employed. Results: Even if the firm does not experiencing financial distress, the study’s findings show that it has no bearing on investment choices, the decision to take debt can help reduce conflicts of interest, strengthen managerial discipline, and provide a positive signal to the market. Leverage affects investment decisions, high leverage can motivate managers to take high-risk projects in the hope that the potential for large profits will enhance the company's financial health. This study found that CSR Disclosure (CSRD) significantly weakens the connection between investment choices and financial difficulties, which may be explained by management’s which is more directed at financial recovery than social responsibility when the company faces financial distress. and This study found that CSR Disclosure (CSRD) significantly strengthens the relationship between leverage and investment decisions, with good CSR disclosure, the company's transparency and accountability increase. Applications/Originality/Value: This study recommends Researchers can use one or more analysis models to determine the level of comparison between relevant analysis models such as the Springate, Zmijewski, and Ohlson models. Future research should explore whether the impact of financial distress on investment decisions varies across different industries or market conditions. There may be certain sectors where financial distress affects investment decisions.